Resident cardiac stem cells on fibrous poly (L-lactide) patch augment cardiac repair via in-patch differentiation and simultaneous migration into infarcted heart tissue. Issue 1 (2018) - Kyung, Heiwon; Kim, Heejung; Chung, Hye-Jin; Lee, Seung Jin; Shim, In Kyong; He, Huining; Yang, Victor C.; Kim, Jong-Tae; Cheong, Soon-ho; Yang, Tae-Hyun; Yang, Young-Il
No abstract available